THE PRINCIPAL'S COMPETENCES IN IMPLEMENTING CULTURAL AND ENVIRONMENTAL MANAGEMENT OF THE SCHOOL IN SDN 033 TARAKAN - Yunus, Muhammad; Andari, Kadek Dewi Wahyuni; Addinul Islam, Muhammad (Jurnal Pendidikan Indonesia, 2017)
In the National Education System Act of 2003, there was a shift in the paradigm of education from centralized to decentralized, commonly referred to as School Based Management (SBM). With the law, the greater the role of headmaster in establishing various policies, one of which concerns the management of school culture and environment. Therefore the principal must have some competences in performing his duties. The type of research used is descriptive qualitative research conducted at SDN 033 Tarakan in the academic year 2016/2017. Sources of research are primary and secondary data. Informants in the study were principals, two teachers, two students, TU staff, school committees and school supervisors. Data collection techniques in this study are interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. Based on the data analysis, the first research is the competence of the principal personality that can be said to be good, but the discipline aspect still needs to be improved. Second is the social competence of the principal is limited to cooperation with committees and guardians. Third is the managerial competence carried out from planning, organizing, implementation, and supervision. Fourth is the competence of supervision where supervision is done 2 times in a year. Fifth is the entrepreneurial competence, there are some efforts of the principal in school financing.